Physical and Oxidative Stability of Uncoated and Chitosan-Coated Liposomes Containing Grape Seed Extract - Jochen Weiss; Nina Rahn; Monika Gibis (MDPI AG, 2013)
Polyphenol-rich grape seed extract (0.1 w/w%) was incorporated in liposomes (1 w/w% soy lecithin) by high pressure homogenization (22,500 psi) and coated with chitosan (0.1 w/w%). Primary liposomes and chitosan-coated secondary liposomes containing grape seed extract showed good physical stability during 98 days of storage. Most of the polyphenols were incorporated in the shell of the liposomes (85.4%), whereas only 7.6% of the polyphenols of grape seed extract were located in the interior of the liposomes. Coating with chitosan did not change the polyphenol content in the liposomes (86.6%). The uncoated liposomes without grape seed extract were highly prone to lipid oxidation. The cationic chitosan coating, however, improved the oxidative stability to some extent, due to its ability to repel pro-oxidant metals. Encapsulated grape seed extract showed high antioxidant activity in both primary and secondary liposomes, which may be attributed to its polyphenol content. In conclusion, the best chemical stability of liposomes can be achieved using a combination of grape seed extract and chitosan.